REACTION PATH MODELLING IN THE AS-S SYSTEM: A CASE STUDY FOR GEOTHERMAL AS TRANSPORT - Cleverley J.S.; Benning L.G.; Mountain B.W. (My University, 2003)
Geochemical speciation and reaction path modelling with the Geochemists Workbench (GWB) software was used to investigate zonal As sulphide mineral precipitation and As transport in an active geothermal field, the Uzon Caldera, Kamchatka. A new compilation and critical review of published experimental and theoretical thermodynamic data for As phases was used to modify and update a SUPCRT92 database with important missing phases. The equilibrium constants for these As phases were then added or modified in the current GWB database. Speciation calculations predict that the sampled fluids are undersaturated with respect to As phases and aqueous As is dominantly transported as the complex H3AsO3(aq) and to a lesser extent the As sulphide complexes As2S3(aq), HAs2S4− and As2S42−. Modelling the changes in concentration of dissolved As between the samples (0.2–8.6 mg/kg) indicates a strong dependence on redox (log O2(g) from −53 to −60) and temperature (95–65 °C), and illustrates the importance of mixing between the hydrothermal fluid and an oxygenated fluid. Reaction path models that follow the cooling of a H2S(aq) dominated, As enriched (15 mg/kg) fluids from 125 to 25 °C, with sliding redox from log O2(g) −55 to −60, predict the mineral paragenesis: (native As+pyrite)−(realgar+pyrite)−(orpiment+pyrite)−(pyrite). This mineral sequence closely resembles the natural layering observed in the Uzon Caldera. Although field measurements contain a lower reduced S concentration than the model, the error margin in the measured sulphide inherent from in situ oxidation during sampling is enough to account for the discrepancy. Despite assumptions in fluid parameters and modelling approaches, as well as deficiencies in the thermodynamic data and an equilibrium approach, this study has shown that acceptable and useful analogues for natural As-rich systems can be developed.